Estimating utility-consistent poverty in Madagascar, 2001-10 - David Stifel; Tiaray Razafimanantena; Faly Rakotomanana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We adapt the standardized Poverty Line Estimation Analytical Software-PLEASe computer code stream based on Arndt and Simler's (2010) utility-consistent approach to measuring consumption poverty in order to analyse poverty in Madagascar in 2001, 2005, and 2010. This paper documents how the utility-consistent approach to inter-temporal and spatial deflation differs from the approach undertaken by the national statistical office to produce the official poverty estimates and how the trends in these estimates differ substantially. Further, we illustrate the importance of addressing extreme values for calculating unit prices, and how to handle redistricting when conducting revealed preference tests of the utility-consistency of not only regionally estimated poverty lines (i.e. do the consumption patterns in other spatial domains cost no less than the own-domain consumption patterns when both are evaluated at own-domain prices), but also of poverty lines over time.
Keywords: D63; I32; O55; 330; poverty measurement; utility-consistent poverty lines; Madagascar